International Experience of Legal Regulation of Liability for Insult of Police Officers and Possibilities of Its Use in Ukraine - K. L. Buhaichuk (Law and Safety)
The article highlights the problem of the need to strengthen the legal protection of employees of the National Police of Ukraine, who are subjected to illegal encroachments on their honor and dignity while performing their official duties.